Institutions Rule The Primacy of Institutions Over Integration and Geography in Economic Development - Subramanian, Arvind (International Monetary Fund, 2002)
We estimate the respective contributions of institutions, geography, and trade in determining cross-country income levels using recently developed instruments for institutions and trade. Our results indicate that the quality of institutions ""trumps"" everything else. Controlling for institutions, geography have at best weak direct effects on incomes, although it has a strong indirect effect through institutions. Similarly, controlling for institutions, trade has a negative, albeit, insignificant direct effect on income, although trade too has a positive effect on institutional quality. We relate our results to recent literature, and where differences exist, trace their origins to choices on samples, specification, and instrumentation